Enhanced enzymatic saccharification and ethanol production of corn stover via pretreatment with urea and steam explosion. (May 2023) - Zhang, Hongqiong; Zhang, Rui; Song, Yunong; Miu, Xinying; Zhang, Quanguo; Qu, Jingbo; Sun, Yong
Graphical abstract: Highlights: Impact of urea and steam explosion on corn stover pretreatment was investigated. Optimal pretreatment improved the enzymatic hydrolysis of corn stover. Using 4.87% urea and 1.22 MPa pressure was optimal for ethanol production. The ethanol fermentation sugar alcohol conversion rate was 48.30%. Abstract: Enhancing the degradation of lignocellulosic structure is essential for the efficient use of corn stover. This study investigated the effects of using urea combined with steam explosion on the enzymatic hydrolysis and ethanol production of corn stover. The results demonstrated that 4.87% urea addition and 1.22 MPa steam pressure were optimal for ethanol production. The highest reducing sugar yield (350.12 mg/g) was increased by 116.42% (p < 0.05), and the corresponding degradation rates of cellulose, hemicellulose, and lignin in pretreated corn stover were increased by 40.26%, 45.89% and 53.71% compared with the untreated corn stover (p < 0.05). Moreover, the maximal sugar alcohol conversion rate was approximately 48.3%, and the ethanol yield reached 66.5%. In addition, the key functional groups in corn stover lignin under combined pretreatment were identified. These findings offer new insights into corn stover pretreatment and can help develop feasible technologies to enhance ethanol production.